O ZAPOŻYCZENIACH LEKSYKALNYCH Z JĘZYKA ROSYJSKIEGO W POLSZCZYŹNIE MIĘDZYWOJENNEJ. NA MATERIALE TYGODNIKA ILUSTROWANEGO - Joachimiak-Prażanowska, Joanna (Acta Neophilologica, 2015)
This article presents lexical borrowings from the Russian language, excerpted from Tygodnik Ilustrowany, a commonly known Warsaw-based weekly. The research analysis was conducted on the words excerpted from the earliest editions of this weekly published over one year, issued in the Republic of Poland, beginning with 1918 when the country regained independence. The author of the study aimed to investigate whether a long-term influence of the Russian language on Polish, particularly in the period of annexations, manifested itself in the Polish language of the first part of the 20th century. The author collected 54 Russicisms, evident in 216 examples. In the collected linguistic material Russian lexis is distinctly dominating. Its application in texts about Russia is fully justified and unavoidable. The lexis consists of historisms, Sovietisms and other words referring to Russian reality, such as: cerkiew or dziesięcina, that entered Polish vocabulary.